2023
DOI: 10.1108/srj-09-2022-0376
|View full text |Cite
|
Sign up to set email alerts
|

CSR initiatives and stakeholder engagement amidst COVID-19 pandemic: insights using content analysis and literature review

Abstract: Purpose The coronavirus disease (COVID-19) has impacted all economies, businesses and societies. The purpose of this paper is to analyze and present a case for corporate social responsibility (CSR) in terms of its relevance amidst the turmoil caused by the pandemic. Design/methodology/approach The authors use a directed content analysis approach to retrieve relevant information from news articles using Thomson Reuters’ Eikon® and Bloomberg® databases. Based on stakeholder theory, the authors evaluate some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 91 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…Based on the above, this study is distinct from previous studies and significantly advances theoretical understanding by synthesizing insights from different theories and perspectives. For instance, this study advances stakeholder theory by confirming that employees are the agents responsible for performing CSR activities; therefore, the success of companies' CSR initiatives depends on their employees' behaviors and attitudes [37][38][39]. Further, this study highlights the relationship between a company's social performance and high-performance work systems in conjunction with other variables, which has been overlooked in previous research [15,31,32].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Based on the above, this study is distinct from previous studies and significantly advances theoretical understanding by synthesizing insights from different theories and perspectives. For instance, this study advances stakeholder theory by confirming that employees are the agents responsible for performing CSR activities; therefore, the success of companies' CSR initiatives depends on their employees' behaviors and attitudes [37][38][39]. Further, this study highlights the relationship between a company's social performance and high-performance work systems in conjunction with other variables, which has been overlooked in previous research [15,31,32].…”
Section: Discussionmentioning
confidence: 54%
“…Corporate social responsibility (CSR) is structured around managing various stakeholders, not just individual shareholders [37]. According to stakeholder theory, companies should strive for social good beyond basic economic interests, catering to various stakeholders [38]. This study specifically focuses on employees among these diverse stakeholders.…”
Section: Perception Of Corporate Social Responsibility (Csr)mentioning
confidence: 99%
“…Several studies have found a positive relationship between SE and social performance and its crucial role in shaping a CSR culture (Doni et al , 2022; Agudo‐Valiente et al , 2015). Furthermore, its importance has also been emphasised during the COVID-19 pandemic (Hasan et al , 2023; Momin et al , 2022). In this direction, recent literature seems to highlight the ability of the SE to co-create shared value, i.e.…”
Section: State Of Art On Stakeholder Engagement In Sustainability Rep...mentioning
confidence: 99%